The effect of difficulty and execution scores on total ranking during 2019 Rhythmic Gymnastics World Championships - Örs, B. S. (African Educational Research Journal, 2020)
Rhythmic gymnastics (RG) is a competitive sport and competition results include multiple components such as difficulty (D) and execution (E) scores. Both coaches and researchers should consider the components of performance scores separately. The aim of the current study was to identify the most indicative apparatus score on total ranking in the individual all-around finals of 37th RG World Championships (WCh), 2019, Baku, Azerbaijan and to determine the most important D and/or E scores on overall ranking. Total of 312 scores of 24gymnasts competed at individual all-around finals were analyzed. Correlations among total qualification, total D, total E, and total apparatus scores of each apparatus were determined by Pearson correlation analysis. Multiple regression analysis was used and model-fitting performance was assessed by coefficient of determination (R2). When correlations among total qualification score and total D, total E scores of each apparatus were analyzed moderate and strong relationships were found (p < 0.001). The percentages that D and E scores explained the total score ranged between 79.3 and 44%. Total ball D score explained 79.3% of the variability in standings and it was the best predictor score. Total ribbon E score was found to be the second effective score on ranking (71%). Finally, total hoop E score had the least effect by 44%. Apart from these, two different total score estimation models that trainers/gymnasts may use practically were enhanced during this study.